PENGARUH PENERAPAN PEMBELAJARAN E-LEARNING TERHADAP KEMANDIRIAN DAN MINAT BELAJAR MAHASISWA PADA MATA KULIAH WAWASAN DAN KAJIAN MIPA - Anggiyani Ratnaningtyas Eka Nugraheni; Dina Dina (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
Abstract The aim of this study was to determine the effect of the implementation of e-learning to the students’ independence and interests in Science insight and Study Course. The used method was experimental post-test only control group design by questionnaire sheets. The subjects were Chemistry Education students year 2015. The results of the hypothesis-test showed that there are no significant differences of independence and interest in both of groups. However, the results of descriptive data analysis showed that the average students’ independence and interest in the experimental was higher than the control group. The experimental group mean of 3.67 (good), while the control group average of 3.48 which are at the same category. Average students’ interest in the experimental group of 4.21 (very good), while the average in the control group at 4.08 (good). In addition, based on the questionnaire of students’ responses toward e-learning obtained mean of 4.51 (very good). Keywords: e-learning; learning independent; learning interest Abstrak Tujuan penelitian ini adalah untuk mengetahui pengaruh penerapan pembelajaran e-learning terhadap kemandirian dan minat belajar mahasiswa pada Mata Kuliah Wawasan dan Kajian MIPA. Metode penelitian yang digunakan adalah eksperimen dengan post-test only control group design dan instrumen lembar angket. Subyek dalam penelitian ini adalah mahasiswa Pendidikan Kimia angkatan 2015. Hasil uji hipotesis menunjukkan tidak ada perbedaan yang signifikan antara kemandirian dan minat belajar pada kedua kelompok. Namun, hasil analisis data deskriptif menunjukkan bahwa rerata kemandirian dan minat belajar mahasiswa pada kelompok eksperimen lebih tinggi dibandingkan kelompok kontrol. Rerata kelompok eksperimen sebesar 3,67 (baik), sedangkan rerata kelompok kontrol sebesar 3,48 yang berada pada kategori yang sama. Rerata minat belajar mahasiswa pada kelompok eksperimen sebesar 4,21 (sangat baik), sedangkan rerata pada kelompok kontrol sebesar 4,08 (baik). Selain itu, berdasarkan angket respon mahasiswa terhadap pembelajaran e-learning diperoleh rerata sebesar 4,51 (sangat baik). Kata Kunci: pembelajaran e-learning; kemandirian belajar; minat belajar Permalink/DOI: http://dx.doi.org/10.15408/es.v9i1.5458